Here we are : notes for living on planet Earth - Jeffers, Oliver (New York, NY : Philomel Books, 2017)
"In this salutation from Earth, the chronicler gives a tour of the planet and introduces those who call it home"--OCLC.
New York Times
Publishers Weekly Annex
School Library Journal
New York Times, January 2018
Publishers Weekly Annex, October 2017
School Library Journal, November 2017
Keywords: Conduct of life -- Juvenile fiction; Parent and child -- Juvenile fiction; Conduct of life -- Fiction; Parent and child -- Fiction; Conduct of life -- Fiction; Parent-child relationship -- Fiction; Earth (Planet) -- Juvenile fiction; Earth (Planet) -- Fiction; Earth -- Fiction; Picture books